Editorial - Gómez Botero, Maryory Astrid (Revista Facultad de Ingeniería Universidad de Antioquia, 2018)
Nowadays, Artificial Intelligence (AI) is not just part of the plot of science fiction movies, but a real and important component of different devices and systems which we interact with every day. The work of computer scientists, mathematicians and engineers has allowed computers to interplay with humans through a kind of “conversation”, using speech recognition algorithms and voice synthesizers, which make users able to perform web searches or phone calls even without touching their phones. This is just one of the many examples where (AI) has become part of our lives. AI comprises many fields including robotics, natural language processing, artificial vision, expert systems, evolutionary computations, machine learning, speech processing, among others. Although many practical applications of AI involve the combination of several of these subfields, perhaps the one that has achieved more interest in recent years is Machine Learning (ML).